Integrasi Sistem Energi Terbarukan dan Penyimpanan untuk Meningkatkan Efisiensi Konversi Energi pada Mikrogrid - Ryan Effendi (Universitas Islam Raden Rahmat, Malang, 2024)
This study delves into the role of integrating renewable energy systems such as solar panels, wind turbines, with storage technology in enhancing energy conversion efficiency in microgrids. Through a comprehensive literature review, both experimental and analytical findings emphasize that this amalgamation can reduce energy losses commonly observed in conventional microgrids. Its positive impacts extend beyond mere efficiency improvements, strengthening the overall stability and reliability of the microgrid. Implications of this integration encompass increased availability of clean energy and the potential to mitigate blackout incidents within microgrids. The study supports the direction towards developing more sustainable and efficient energy systems in the future.